Pengaruh Literasi Digital dan Kompetensi terhadap Produktivitas Karyawan pada PT. PLN (Persero) ULP Takalar - Fathiyah Ainil Mardiyah; Muchriady Muchran; Nurinaya Nurinaya (Jurnal Ekonomi Manajemen Akuntansi, 2026)
This Study aims to analyze the effect of digital literacy and competence on employee productivity at PT PLN (Persero) Customer Service Unit (ULP) Takalar. This study employs a quantitative approach using a survey method. The population consists of all employees of PT PLN (Persero) ULP Takalar, and a census sampling technique was applied, meaning all members of the population were selected as respondents. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that digital literacy has a positive and significant effect on employee productivity. This means that the better the employees’ ability to understand and utilize digital technology, the higher their level of productivity. In contrast, employee competence was found to have a negative and significant effect on productivity. This finding suggests that increasing competence does not automatically lead to higher productivity if it is not supported by other relevant factors. These findings imply that improving competence without proper job placement, effective task management, and optimal utilization of skills may actually reduce employee productivity. Therefore, it is recommended that PT PLN (Persero) ULP Takalar not only enhance employees’ digital literacy and competence but also ensure alignment between competencies and job requirements through more effective human resource management in order to improve overall productivity